Democracy and inter-regional trade enhancement in Sub-Saharan Africa: Gravity model - Nazif Durmaz; John Kagochi (Economies, 2018)
There has been considerable research on the effect of democracy on trade openness since the 1980s when development strategies toward free trade and democracy were rapidly adopted in developing countries. Most studies have focused on Asian, Latin American, and former soviet bloc countries and few studies have focused on Sub-Saharan Africa (SSA). This study is an attempt to fill that gap and uses a gravity model approach to test the effects of democracy in SSA on trade. Our results show that democracy has substantial impact on openness to trade and SSA democratic countries will trade more with other countries irrespective of their level of democracy, when compared to non-democratic countries. The results do not vary much even when we use different sources of democracy variable. Also, democratic countries trade more among each other perhaps due to having a shared business environment.
Keywords: F15; C55; O50; 330; gravity model; panel data; democracy; trade openness; Sub-Saharan Africa